Pengaruh Penerapan Model Problem Based Learning terhadap Kemampuan Berfikir Kritis Siswa pada Pembelajaran Tematik Kelas 5 SD N Jomblangan - Setyawan, Arya Dani; Atmaja, Dimas Tri; Arief, Ardian; Purnamasari, Dyan Indah; Wardani, Kristi; Marwanti, Endah (Piramida Akademi, 2023)
This article is a quasi-experiment with a non-equipvalent control group design. The data obtained in this article are from SD Negeri Jomblangan Banguntapan, Bantul, Yogyakarta. The subject used is the fifth grade students of SD Negeri Jomblangan. The object used is the ability to think critically. Data collection techniques used are observation techniques, tests and documentation. The data analysis technique used is quantitative descriptive. The results of the analysis show that students' critical thinking skills have increased by using the Problem Based Learning (PBL) model. This is evidenced by an increase in critical thinking skills which can be seen from the average score of the test results. The average value of the pretest was 70.14, after the action was taken using the PBL model the average value increased to 86.14. The results of the t-test for experimental pre-test data and control pre-test showed a sig value of 0.332 (sig value> 0.05) or t count <t table (0.980 <1.67), that is, there was no difference in critical thinking skills during the pre-test between the experimental class and the control class. This means that the initial ability to think critically is the same, so different treatments may be given. From these results it can be seen that there is an increase in critical thinking skills in thematic learning with PPKN class V SDN Jomblangan Banguntapan Bantul.